Oxford handbook of psychiatry - Semple, David; Smyth, Roger (Oxford University Press, 2011)
This handbook provides portable reassurance to doctors beginning psychiatry. There is helpful advice for the management of difficult and urgent situations, and the text is peppered with clinical observations on the practice of clinical psychiatry and guidance based upon the experience of the authors